Factors Affecting Capital Structure Of Manufacturing Companies In Indonesia And Malaysia - Sugianto, Nadzma Safira Putri; Moin, Abdul (Jurnal Ilmiah Ekonomi Dan Bisnis, 2025)
Differences in macroeconomic conditions, monetary policy, and financial regulation between Indonesia and Malaysia shape different capital structure patterns in both countries. This study aims to analyze the effect of economic conditions and government policies on the capital structure of manufacturing companies in Indonesia and Malaysia. The sample is selected using purposive sampling technique from Osiris database and stock exchanges of both countries. The manufacturing sector is the focus due to its large contribution to the economy and efforts to optimize its funding. The results show that in Malaysia, factors such as growth, liquidity, profitability, size, and age of the firm affect capital structure, while in Indonesia only size and age are significant. The combined analysis with Fixed Effect found that only firm size is consistently influential, while other variables are not significant due to differences in economic context and financial system. These findings highlight the importance of considering local context in capital structure analysis.